Derivatif Action sebagai Upaya Perlindungan Hukum bagi Perusahaan PMA - Firdaus, Muhammad Reza (Universitas Ekasakti, 2023)
In running a company, the Board of Directors and Commissioners are certainly not exempt from errors, mismanagement, or fraudulent activities that may lead to actions detrimental to the company and shareholders. Therefore, there must be legal protection for the company and its shareholders. One solution to this legal protection issue is derivative lawsuits, as exemplified by Prosper China Investments Limited. Based on the above description, the author is interested in conducting research and discussion on whether the derivative action filed by PT Merge Energy Sources Development constitutes a form of legal protection for a Foreign Investment Company (PMA). Additionally, it examines the challenges and issues associated with derivative actions within the legal provisions in Indonesia. This research employs a normative juridical method, utilizing secondary data through a literature review. The findings of this study indicate that the derivative action taken by PT. Merge Energy Sources Development's shareholders is in accordance with applicable laws, as it is regulated in Article 97, paragraph (6) of the Company Law concerning directorial lawsuits and Article 114, paragraph (6) of the Company Law concerning commissioner lawsuits. However, the mechanism of derivative action as a legal protection tool in Indonesia is not yet sufficient, primarily due to the limited regulations regarding derivative actions in Indonesia compared to Common Law countries, and even in comparison to Civil Law countries.